MyPlate Foods to Increase: Whole Grains - Jonathan Holzinger; Karla Shelnutt (EDIS)
A higher intake of whole grains is associated with a lower body mass index (BMI) and distribution of fat around the abdomen, but only 7% of American adults meet the recommended intake. This 3-page fact sheet provides information on whole grains and their health benefits as well as how to include whole grains in your diet. Written by Jonathan Holzinger and Karla Shelnutt, and published by the UF Department of Family, Youth and Community Sciences, March 2012.